The pathophysiology of UVA-light induced hyperalgesia - Themistocleus, Andreas Constantinos (My University, 2009)
In this thesis I describe the development of an animal model of sustained hyperalgesia induced by exposure to ultraviolet (UV) A light to the rat’s tail, and the role of the Cfibre barrage and peripheral afferent fibre sensitization in this model of hyperalgesia. Exposure of rats’ tails to UVA-light caused hyperalgesia to a noxious thermal challenge, immersion of the rats’ tails into 49°C water, and a noxious mechanical challenge, application of a static force of 3.9N by a bar algometer onto the rats’ tails. The hyperalgesia to the thermal challenge lasted eight days and hyperalgesia to the mechanical challenge continued for up to 16 days. Despite the sustained hyperalgesia, rats exposed to UVA-light showed no overt signs of morbidity as they gained weight normally and were mobile throughout the study. Histological examination of rat tail tissue showed mild, chronic inflammation in rats exposed to UVA-light and in rats that had their tails covered with a protective layer of aluminium foil during UVA-light exposure. This inflammation was therefore not responsible for the behavioural hyperalgesia. To investigate the role of C-fibre barrage in the development of hyperalgesia after UVA-light exposure, I pre-emptively blocked C-fibre activation during UVA-light exposure with the local anaesthetic bupivacaine. Injection of bupivacaine (1ml of 0.5%), into the base of the tail prevented the development of thermal hyperalgesia to tail immersion in 49°C water. However, it did not prevent the development of hyperalgesia to a noxious punctate challenge. Thus the sustained mechanical hyperalgesia did not depend on the activation of the C-fibre barrage, but thermal hyperalgesia did depend on the activation of a C-fibre barrage during the conditioning event of UVA-light exposure. Lastly, in rats anaesthetised with enflurane, I examined the responses of coccygeal primary afferent fibres to noxious thermal and mechanical stimulation after UVA-light exposure of their receptive fields on the tail. I investigated only pure nociceptive afferents and ignored those afferents that responded to challenges in the noxious and non-noxious ranges. The peak firing rates and areas under the curve of post-challenge histograms, a measure of neuronal firing over time, of Ad- and C-fibres were increased when noxious blunt and punctate challenges were applied to the rats’ tails after UVA-light exposure, showing that Ad- and C-fibres that encode for noxious mechanical challenges were sensitized. The peak firing rate of C-fibres that were responsive to noxious thermal challenges were not increased after UVA-light exposure. Therefore, thermal hyperalgesia was probably mediated by sensitization of central nervous system neurones. In summary, I developed a model of sustained mechanical and thermal hyperalgesia caused by UVA-light exposure of the rat tail. The thermal hyperalgesia was initiated by the C-fibre barrage, while mechanical hyperalgesia did not depend on the C-fibre barrage and peripheral afferent sensitization of Ad- and C-fibres could account for the mechanical hyperalgesia.
D.Phil. Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: ultraviolet rays; pain; laboratory rats